2018
DOI: 10.18520/cs/v114/i05/1117-1119
|View full text |Cite
|
Sign up to set email alerts
|

Coral-Killing Sponge <i>Terpios hoshinota</i> Invades the Corals of Gulf of Mannar, Southeast India

Abstract: Terpios hoshinota is an encrusting cyanobacteriosponge which grows aggressively over live coral colonies and has been reported to undergo outbreaks which kill corals. In an underwater survey conducted on the reefs of Gulf of Mannar, an outbreak of this coral-invading sponge was witnessed for the first time. It was found invading approximately 5% of the Montipora divaricata colonies (n = 383) at 1 m depth in Vaan Island. The affected site had a high coral cover (85.13%) dominated by montiporids (79.97%). T. hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Since its first occurrence, it has been observed in several coral reef localities around the globe viz. the Great Barrier Reef 3 , Papua New Guinea 4 , Taiwan 5 , Philippines 6 , Indonesia 7 , South China Sea 8,9 , Thailand 6 , Palk Bay (PB)/Gulf of Mannar (GOM) (India) 10–12 , Maldives 13 , Mauritius 14 and our present observation, confirms that the species has further extended its habitat into the pristine atolls of Lakshadweep (Figure 1) (Indian Ocean) and requires urgent attention.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Since its first occurrence, it has been observed in several coral reef localities around the globe viz. the Great Barrier Reef 3 , Papua New Guinea 4 , Taiwan 5 , Philippines 6 , Indonesia 7 , South China Sea 8,9 , Thailand 6 , Palk Bay (PB)/Gulf of Mannar (GOM) (India) 10–12 , Maldives 13 , Mauritius 14 and our present observation, confirms that the species has further extended its habitat into the pristine atolls of Lakshadweep (Figure 1) (Indian Ocean) and requires urgent attention.…”
Section: Introductionsupporting
confidence: 82%
“…Our findings contradict these above statements and is more in line with the findings of Shi et al 8 , who observed T.hoshinota outbreak in unpolluted areas of Yongxing Island (South China Sea). Prevalence of T.hoshinota in the southeastern reefs of India (~800km from Lakshadweep) is due to high anthropogenic stress and its close proximity to mainland 10–12 , however, a similar conclusion cannot be applied in the case of Lakshadweep because of its isolated geography 17 and with comparatively less anthropogenic activities. In terms of host selectivity, the killer sponge has affected several coral species in different parts of the world 1,10,12,14 and in the reefs of Palk Bay (PB), it affected all genus surveyed 10 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The cyanobacterio sponge Terpios hoshinota Rützler & Muzik, 1993 also known as the black disease* (Liao et al 2007) first reported from Guam (Bryan 1973) and later described from the coral reefs of the Ryukyu archipelago (Japan) (Rützler & Muzik 1993) is identified by its gray to blackish encrustations. Since its first occurrence, it has been observed in several coral reef localities around the globe, viz., the Great Barrier Reef (Fujii et al 2011), Papua New Guinea (Ekins et al 2017, Taiwan (Liao et al 2007), Philippines (Plucer-Rosario 1987), Indonesia (De Voogd et al 2013), South China Sea (Shi et al 2012;Hoeksema et al 2014;Yang et al 2018) , Thailand (Plucer-Rosario 1987, Palk Bay (PB)/Gulf of Mannar (GOM) (India) (Thinesh et al 2015(Thinesh et al , 2017Raj et al 2018a), Maldives J TT (Montano et al 2015), Mauritius (Elliott et al 2016) and our present observation, confirms that the species has further extended its habitat into the pristine atolls of Lakshadweep (Image 1) (Arabian Sea) and requires urgent attention.…”
Section: Platinum Open Accessmentioning
confidence: 99%